PENERAPAN MODEL PENGENDALIAN WAKTU DAN BIAYA - . Sunario; . Syahrudin; Riyanny Pratiwi (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2016)
In the city of Pontianak is still continuing development to meet the basic needs adequately. And one of the staples that are needed in daily life - today is the place to stay. From there the developers race - the race to build an ideal area. One of them is the construction of complex De Perdana City is located at Perdana Street Pontianak. The purpose of this paper is to identify and analyze the problems of controlling the form factors - factors that cause delays in the project on construction work in the field so that it can submit management plans and programs of action plans that can be done to address the problem of delay without reducing the quality of the work. Complex housing De Perdana City Pontianak is the type of housing development projects totaling 20 with 160 units. With the design of the coupling or 2 units are designed arm. The construction site is located at Jalan Perdana Pontianak. Funds allocated is Rp. 1.529.428.000, - per unit coupling, with a planned implementation of 200 (two hundred) calendar days, ie after the date of January 6, 2014 until July 27, 2014. One of the duration of the acceleration method that can be used is the method of Earned Value Analisys. Based on current progress report on the project duration 16 weeks, which is based on planning should reach 58.37% turned out to be the reality that occur in the field reached 53.48%, so that the project would be delayed by the deviation between the weights with a weight plan realization was - 4, 89%. While based on the progress report of the new project is expected to be completedbyAugust2014.Alternative acceleration used is the addition of working hours (overtime) to four (4) hours of work and increase the amount of labor. Acceleration duration of the project carried out by two (2) steps, namely: crashing a program that is only held on the activities that are on the critical path analysis and Earned Value namely by conducting compression (pressure) the duration of the project carried on activities that are on track critical without interrupting other work items. Based on the analysis that has been done there is deviation time of 21 days, the total working period to 217 days from 200 days the amount of time the plan with estimated cost is Rp. 1.529428 billion. Controlling the performance observed from week 1 to week 16. An analysis of the week to -16 indicates that the costs were lower than budgeted costs but longer execution time of the schedule plan showed with CPI = 1.01 (CPI> 1) and SPI = 0, 92 (SPI <1 ). The result of the calculation forecasts the project's final cost of Rp. 1,379,493,655.00 with the project completion time back to the original plan of 200 days. Keywords :earned value, crashing programs, delays, acceleration